2009
DOI: 10.2343/geochemj.1.0034
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of organic matter in the Lower Palaeozoic rocks of the Peribaltic Syneclise (Poland)

Abstract: Organic matter occurring in Lower Palaeozoic rocks of variable lithology was investigated for its origin, depositional environment and thermal maturity. Samples from nine boreholes located in the Polish part of the Peribaltic Syneclise were collected for performing Rock-Eval Analysis, palynological investigation for Thermal Alteration Index (TAI), solvent extraction, preparative layer chromatography (PLC) and gas chromatography-mass spectrometry (GC-MS) of aliphatic and aromatic compound fractions. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Thus, we summarize that under unique conditions connected with migration of hydrothermal fluids, the composition of the extractable OM changes significantly, especially in the case of the aromatic fraction. Extracts from Silurian samples of the Polish lowland are characterized by a significantly different molecular composition, with high amounts of alkylnaphthalenes and alkylphenanthrenes, as well as low or nil abundances of phenyl-derivatives (Marynowski et al, 2011b;Skręt and Fabiańska, 2009). The only cause of such a significant molecular transformation can be a specific diagenetic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we summarize that under unique conditions connected with migration of hydrothermal fluids, the composition of the extractable OM changes significantly, especially in the case of the aromatic fraction. Extracts from Silurian samples of the Polish lowland are characterized by a significantly different molecular composition, with high amounts of alkylnaphthalenes and alkylphenanthrenes, as well as low or nil abundances of phenyl-derivatives (Marynowski et al, 2011b;Skręt and Fabiańska, 2009). The only cause of such a significant molecular transformation can be a specific diagenetic process.…”
Section: Discussionmentioning
confidence: 99%
“…Such distributions are typical for Silurian sedimentary OM from the Polish lowland (Skręt and Fabiańska, 2009) and representative for a marine OM type. Regular steranes and hopanes are present in low abundance or are totally absent due to the high maturity range.…”
Section: General Organic Matter Characteristicsmentioning
confidence: 98%
“…to the TTZ (Fig. 4; Kanev et al, 1994;Nehring-Lefeld et al, 1997;Swadowska and Sikorska, 1998;Grotek, 1999Grotek, , 2006Grotek, , 2016Skręt and Fabiańska, 2009;Więcław et al, 2010Więcław et al, , 2012. In all stratigraphic units, thermal maturity increases toward SW correspondingly to the increase of burial depth.…”
Section: Previous Thermal History Studiesmentioning
confidence: 97%
“…Chronostratigraphic subdivisions and absolute ages refer to Gradstein et al (2012) throughout the text. (Grotek, 1999(Grotek, , 2006(Grotek, , 2016Skręt and Fabiańska, 2009;Pletsch et al, 2010).…”
Section: Thermal Modellingmentioning
confidence: 99%
“…These studies revealed a systematic zonation in the degree of diagenesis of Ediacaran to lower Paleozoic rocks that is oriented NE-SW, parallel to the TTZ (Fig. 4; Kanev et al, 1994;Nehring-Lefeld et al, 1997;Swadowska and Sikorska, 1998;Grotek, 1999Grotek, , 2006Grotek, , 2016Skręt and Fabiańska, 2009;Więcław et al, 2010Więcław et al, , 2012. In all stratigraphic units, thermal maturity increases toward the SW corresponding to the increase of burial depth.…”
Section: Previous Thermal History Studiesmentioning
confidence: 97%